The applicability of a multitask boxing program using the BoxMaster ® for Parkinson’s disease - Domingos, Josefa (2016)
"Objective: To test the applicability of a multitasking boxing program using the BoxMaster® in individuals with Parkinson’s disease that combines motor, cognitive and vocal exercises."